Crack Programming: From Chaos to Control: Programmable Crack Patterning with Molecular Order in Polymer Substrates (Adv. Mater. 22/2021). Issue 22 (1st June 2021) - Kim, Hyun; Abdelrahman, Mustafa K.; Choi, Joonmyung; Kim, Hongdeok; Maeng, Jimin; Wang, Suitu; Javed, Mahjabeen; Rivera‐Tarazona, Laura K.; Lee, Habeom; Ko, Seung Hwan; Ware, Taylor H.
Abstract : Cracking is typically an uncontrolled material failure process. In article number 2008434, Hyun Kim, Taylor H. Ware, and co‐workers describe a process that enables unprecedented control of crack formation. By depositing thin‐film chromium on photoaligned liquid‐crystal polymer networks, patterns of cracks on the surface of a polymer can be freely programmed in a high‐resolution and high‐throughput manner. This crack programming process provides new opportunities for unconventional microfabrication. The image depicts light transmitted through a polymer film coated with chromium with azimuthally patterned cracks.